LEVEL OF HABITUAL PHYSICAL ACTIVITY IN 8-9 YEARS OLD SCHOOLCHILDREN FROM SPAIN AND INDIA - López Sánchez, Guillermo Felipe (2016)
The level of physical activity of people is a very important issue internationally. The aim of this study was to analyze and compare the level of habitual physical activity in 8-9 years old schoolchildren from Spain and India. With this purpose, it was administered the questionnaire PACE (Physician-based Assessment and Counseling for Exercise) in a sample of 85 schoolchildren (44 from Spain and 41 from India). The results showed that the sample studied does not do enough physical activity, according to the recommendations of the World Health Organization, as they do at least 60 minutes of physical activity; only an average of 3.13 days/week (SD=1.91). 8-year-old schoolchildren do more physical activity than 9-year-old schoolchildren in both countries; boys do more physical activity than girls in both countries; schoolchildren from India do more physical activity than schoolchildren from Spain. Therefore, it is concluded that the level of physical activity is insufficient, decreases slightly with the age and is higher in India.